INVESTIGATION OF STUDENTS' BEHAVIOR IN MATHEMATICAL PROBLEM SOLVING - Yulyanti Harisman; Muchamad Subali Noto; Wahyu Hidayat (IKIP Siliwangi and I-MES, 2021)
This study is a qualitative research by using the descriptive method that aims to examine the behaviour of eighteen students in Bandung, Indonesia. Six issues related to geometry were given to eighteen of second-grade junior high school students with heterogeneous abilities. The problems given to the students contained all of the problem-solving strategies such as guessing and checking, make a picture, make a list, make a table, working backwards, looking patterns, and using a logical reason, solving simple problems and making questions. Data collection was conducted through mathematical problem-solving tests, recording students’ presentations, and interviewing among researchers and students after doing the problems. The result of recording was a video during the presentation process, and the interview would explore their understanding of the given problems to see the behaviour used by subjects of the research. The data in this research showed that many students’ behaviour identified; in the relevant literature, there are terms of the behaviour of problem-solving naive, routine, and sophisticated. However, the category